γ*γ→π([eta], [eta]) transition form factors - Melikhov, Dmitri; Stech, Berthold (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
The surprising results by the BABAR Collaboration on the πγ transition form factor require new thoughts about the high-Q2 dependence of the form factors with virtual photons. We make use of the anomaly sum rule [J. Horejsi and O. Teryaev, Z. Phys. C 65, 691 (1995).] which relates the hadron spectral density to the axial anomaly [S. Adler, Phys. Rev. 177, 2426 (1969); J. S. Bell and R. Jackiw, Nuovo Cimento A 60, 47 (1969).]. We study the quark-hadron duality relation for this sum rule and find out that the increase of the rescaled form factor Q2Fπγ(Q2)∼log (Q2) suggested by the BABAR data requires the presence of a 1/s-correction term in the relation between the one-loop spectral density and the hadron-continuum spectral density.